Sex differences in hippocampal β-adrenergic receptor subtypes drive retrieval, retention, and learning of cocaine-associated memories - Berry, Melanie M.; Miller, Beau; Kelsen, Silvia; Cockrell, Carlee; Kohtz, Amy Stave (Frontiers in Behavioral Neuroscience, 2024)
Background: Drug seeking behavior occurs in response to environmental contexts and drugassociated cues. The presence of these pervasive stimuli impedes abstinence success. β-adrenergic receptors (β-ARs) have a long-standing historical implication in driving processes associated with contextual memories, including drug-associated memories in substance use disorders. However, sex differences in the role of β-adrenergic receptors in drug memories remain unknown.Prior reports indicate a selective role for β2-ARs in retrieval and retention of contextual drug memories in males, and substantial sex differences exist in the expression of β-ARs of male and female rats. Therefore, we hypothesized that there are sex differences in selective recruitment of β-ARs during different stages of memory encoding and retrieval.The role of β-ARs in driving retrieval and learning of contextual cocaine memories was investigated using cocaine conditioned place preference (CPP) in adult male and female Sprague-Dawley rats. Rats were infused directly to the dorsal hippocampus with Propranolol (β1 and β2) or ICI-118,551 (β1) and/or Betaxolol (β2), immediately prior to testing (retrieval), or paired to each cocaine (10mg/kp, IP) conditioning session (learning).In males, administration of either β1, β2, or combined β1 and β2-ARs before the initial CPP testing reduced the expression of a CPP compared to vehicle administration. In females, β2-ARs transiently decreased CPP memories, whereas β1 had long lasting but not immediate effects to decrease CPP memories. Additionally, β1 and combined β1 and β2-ARs had immediate and persistent effects to decrease CPP memory expression. DG Fos+ neurons predicted cocaine CPP expression in males, whereas CA1 and CA3 Fos+ neurons predicted cocaine CPP expression in females.There are significant sex differences in the role of dorsal hippocampus β-ARs in the encoding and expression of cocaine conditioned place preference. Furthermore, sub regions of the dorsal hippocampus appear to activate differently between male and female rats during CPP. Therefore DG, CA3, and CA1 may have separate region-and sex-specific impacts on driving drug-associated, or context-associated cues.